2019
DOI: 10.31014/aior.1992.02.01.75
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bankruptcy Probability, Auditor Switching and Company Size Toward Audit Delay

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
3
0
3
Order By: Relevance
“…Hence, it takes more time to carry out the audit process. Research results in this are in line with the opinion of Nova et al [20], Putra and Wilopo [21] and Benimahd et al [22].…”
Section: Results Of Hypothesis Testing 3 4 Andsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, it takes more time to carry out the audit process. Research results in this are in line with the opinion of Nova et al [20], Putra and Wilopo [21] and Benimahd et al [22].…”
Section: Results Of Hypothesis Testing 3 4 Andsupporting
confidence: 92%
“…Research on auditors witching has been carried out by Nova et al [20], Putra and Wilopo [21], and Benimahd et al [22] showed that the auditor's witching had a significant positive effect on audit delay. A positive relationship indicates that if there is a change of auditors, the audit completion time will increase because the new auditors need more time to study the systems and accounts of the audited company.…”
Section: Effect Of Auditor Switching On Audit Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Perseroan yang berganti auditor sering membutuhkan waktu yang relevan bagi auditor baru untuk memahami lingkungan perseroan yang diaudit. Nova & Azwardi (2019), V. A. Putra & Wilopo (2018) dan Banimahd et al (2012) dalam penelitiannya mengemukakan bahwa adanya pergantian personel pelaku audit dapat berpengaruh terhadap audit delay.…”
Section: Pendahuluanunclassified
“…Riset membuktikan bahwa dengan mengubah auditor, maka auditor pengganti memerlukan beberapa waktu untuk memahami sistem serta karakteristik usaha klien, sehingga memerlukan waktu lebih dalam pelaksanaan proses auditnya, meskipun kebutuhan waktu lebih tersebut tidak signfikan. Hasil penelitian ini tidak sejalan dengan pendapat Nova & Azwardi (2019), Putra dan Wilopo (2017) dan Banimahd et al (2012) yang mengungkapkan pengubahan auditor berpengaruh positif relevan kepada audit delay. Sutono, Heru Sulistiyo, Bagus Kusuma Ardi (2022).…”
Section: Gambar 2 Hasil Uji Heteroskedastisitasunclassified